Kontribusi dan Peluang Pendidikan Islam pada Era Disrupsi (Analisis Kritis terhadap Sistem Pendidikan Karakter di Indonesia) - Sholikah Sholikah (Institut Agama Islam Al-Hikmah Tuban, 2022)
Various kinds of theories about character education have developed rapidly, their development can be seen from the derivation of character values ​​with various versions. However, until now character education is still a concern of all circles, especially Islamic education. Learning materials and models are developed to reach Indonesia's golden generation in 2045. However, people are still stuttering the technology they face today, with its extraordinary developments. A descriptive-qualitative-interpretive approach, from a variety of scientific sources and literature studies, this scientific article attempts to answer and research the important essence in maintaining the character values ​​of Islamic Education. The conclusion of this study is that Islamic education has an important role in determining the direction of the character education curriculum policy. The challenges are clearly found in advanced technology which continues to develop incessantly. The implementation of character education must be strengthened by the awareness and cooperation of parents, educational institutions and the community. Indonesia's golden generation of 2045 would be achieved if the character learners era Millennial currently guided very well. So that Islamic education has a role in the development of material and learning models.